Alphaworld: moving home - Feely, Jenny (Oxford University Press Melbourne, 2004)
Moving home is a significant life transition that brings a mix of excitement and challenges. The process often starts with careful planning, from sorting through belongings to deciding what to keep, donate, or discard. Packing can feel overwhelming, but it$1 (Bs an opportunity to declutter and refresh your space. Once you arrive at your new home, there$1 (Bs the thrill of exploring a fresh environment and making it your own, whether through decorating or arranging furniture. Amidst the chaos, there$1 (Bs often a sense of nostalgia for the old place, but the promise of new memories can make the journey worthwhile. Connecting with neighbors and settling into a new community adds to the adventure, making it a time of both change and opportunity.s